L’eau : ressource naturelle, ressource politique ? - Vincent Bos; Kyra Grieco (Caravelle, 2018)
The mobilizations against mining extraction constitute a favourable moment to observe the social construction of resources known as “natural”. The conflict related to the project Minas Conga (2011-2016), in the department of Cajamarca in Peru, enables us to analyze the reconstruction of water resources opposed to the mining sector, by numerous agents acting on different scales. By inscribing on several registers: legal, scientific and moral, water is shown as a vital resource to be protected from human greed.